La administración del desarrollo sostenible en el contexto de la economía social de mercado - Vera, José Carlos (2007)
The theory of market social economy appears neatly when dealing with environmental conservation and the search for the wellbeing of the underprivileged. These concepts have been used in various countries and today it is possible to see countries that carefully watch over their environment and have achieved signifi cant social balance. Peru has not been alien to environmental and social concepts and for more than four decades has establishes organizations, designed policies and enacted laws to look at these issues. However, the outcomes have been limited. Among the reasons that explain the ineffectiveness of such regulations and institutions perhaps among the most important are the lack of effective oversight and control over economic agents, and an ineffi cient design of the ways to attain goals through regulations and institutions. For that reason, this paper proposes policy options to correct market outcomes and a way to build institutions that will allow to accomplish the desired goals